Large three‐dimensional ellipsoid sphere‐shaped structure of electrostatic solitary waves in the terrestrial bow shock under condition of Ωce/ωpe < < 1. Issue 13 (10th July 2013) - Li, S. Y.; Zhang, S. F.; Cai, H.; Deng, X. H.; Chen, X. Q.; Zhou, M.; Yang, H. B.
Abstract [1] Several cases of short‐time durational large‐amplitude three‐dimensional (3‐D) electrostatic solitary waves (ESWs) are observed within the transition layer of the terrestrial bow shock by THEMIS/E. Their pulse width is small (0.8–2 ms), but the amplitude is large (greater than 100 mV/m), suggesting a very strong potential drop. Two character angles (θ1 and θ2) are defined to describe the 3‐D characteristics of the ESWs, and it returns results as 76° > θ1 > 27° and 70° > θ2 > 20°, suggesting that the electron potential holes are mainly in 3‐D ellipsoid sphere‐shaped structure, including "pancake‐shaped" structure and "sphere‐shaped" structure. None of the theories commonly used to describe ESWs adequately address these pancake‐shaped and sphere‐shaped three‐dimensional structures observed in the terrestrial bow shock, where ωce < < ωpe in a weak magnetized plasma. The observation of large three‐dimensional ESWs with different spatial structures during small time interval suggests anisotropic distribution of electric potentials and presents evidence of complex wave fluctuation within the bow shock.